PELATIHAN ASESMEN AUTENTIK BAGI GURU SEKOLAH DASAR MUHAMMADIYAH PAKEM SLEMAN - Prihantoro, Agung; Nugroho, Taufik; Nasrudin, Muhammad; Hidayat, Ridwan Nur; Aprilia, Aprilia (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
A kind of learning assessments that has not been done by the teachers of Pakem Muhammadiyah Elementary School, Sleman, Special Province of Yogyakarta is authentic assessment. Therefore, training and workshop of authentic assessment were held for the six teachers of 1—6 grades. Before and after the training and workshop were held, the teachers were pretested and postested. The training and workshop were held in forms of lecturing, discussing and designing authentic assessment. Scores of the pretest and postest were analyzed with Wilcoxon Signed-Rank Test. Ho is the training and workshop do not improve the teachers’ knowledge on authentic assessment. Ho is accepted if P-value < 0,05 with α = 0,05. Because of P-value < α, 0,00027 < 0,05, Ho is accepted. It concludes that the training and workshop do not improve the teachers’ knowledge on authentic assessment. It may be caused of limited durance of the training and workshop.